CHROMOBLASTOMYCOSIS: A NEGLECTED TROPICAL DISEASE - Flavio QUEIROZ-TELLES (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
SUMMARYChromoblastomycosis (CMB) is a chronic fungal infection of the skin and the subcutaneous tissue caused by a transcutaneous traumatic inoculation of a specific group of dematiaceous fungi occurring mainly in tropical and subtropical zones worldwide. If not diagnosed at early stages, patients with CBM require long term therapy with systemic antifungals, sometimes associated with physical methods. Unlike other neglected endemic mycoses, comparative clinical trials have not been performed for this disease. Nowadays, therapy is based on a few open trials and on expert opinion. Itraconazole either as monotherapy or associated with other drugs, or with physical methods, is widely used. Recently, photodynamic therapy has been successfully employed in combination with antifungals in patients presenting with CBM. In the present revision the most used therapeutic options against CBM are reviewed as well as the several factors that may have impact on the patient's outcome.